Pengaruh Profitabilitas, Struktur Aktiva, Umur Perusahaan, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Sektor Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2022) - Jihan Hasan; Rinny Meidiyustiani (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aims to determine the effect of profitability, asset structure, company age, and company size on company value in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2022 period as many as 85 companies. The data used in this study was obtained from financial statement data and annual reports. The population in this study is property and real estate sector companies listed on the Indonesia Stock Exchange. The sampling technique used was the purposive sampling method and obtained 258 sample data from 43 companies. The analysis technique used in this study is a multiple linear regression analysis test using the Statistical Package for the Social Sciences (SPSS) program version 22. The results of this study show that profitability and company age have a positive and significant effect on company value, while asset structure and company size have no effect on company value.